2022
DOI: 10.1186/s10020-022-00445-0
|View full text |Cite
|
Sign up to set email alerts
|

The pyroptosis-related gene signature predicts prognosis and indicates immune activity in hepatocellular carcinoma

Abstract: Background Hepatocellular carcinoma (HCC) remains one of the most common malignant tumors with poor survival. Pyroptosis is a kind of programmed cell death that can regulate the proliferation, invasion, and metastasis of tumor cells. However, the expression levels of pyroptosis-related genes (PRGs) in HCC and their relationship with prognosis are still unclear. Methods Our study identified 35 PRGs through bioinformatics analysis that were different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 53 publications
2
39
0
Order By: Relevance
“…This article included 81 genes related to pyroptosis based on previous studies [ 16 18 ]. We searched for genes associated with pyroptosis in DEGs by mapping Venn diagrams ( http://bioinformatics.psb.ugent.be/webtools/Venn/ ).…”
Section: Methodsmentioning
confidence: 99%
“…This article included 81 genes related to pyroptosis based on previous studies [ 16 18 ]. We searched for genes associated with pyroptosis in DEGs by mapping Venn diagrams ( http://bioinformatics.psb.ugent.be/webtools/Venn/ ).…”
Section: Methodsmentioning
confidence: 99%
“…This situation raised great uncertainties regarding the exact functions of pyroptosis in different kinds of tumors. Furthermore, as a matter of fact, previous studies paid much more attention to the roles of PRGs in solid carcinomas [e.g., hepatocellular carcinoma ( Deng et al, 2022 ), breast cancer ( Xu D. et al, 2021 ), lung adenocarcinoma ( Lin W. et al, 2021 ), and colon adenocarcinoma ( Luo et al, 2021 )] with few studies, however, focusing on non-solid tumor such as AML. Therefore, the present study provided a novel signature featuring six PRGs ( CASP3 , ELANE , GSDMA , PYCARD , VDR , and NOD1 ) that exactly and independently predict OS in AML patients, which will further contribute to driving the progress of individualized prevention and treatment of AML.…”
Section: Discussionmentioning
confidence: 99%
“…The results of qRT-PCR suggested that BAK1, BAX, CHMP2A, GSDME, IL1A, TP53, TP63, GPX4, PRKACA and SCAF11 were highly expressed in HCC tissues. Some related studies have been on pyroptosis-related gene signatures in HCC, which proved that PRGs played important roles in predicting the prognosis of HCC [6][7][8]. Unlike these studies, we firstly added mutation data analysis of PRGs, and the ICGC-LIRI-JP dataset to verify the validity of the model.…”
Section: Discussionmentioning
confidence: 99%
“…Pyroptosis, designated as a novel programmed cell death pathway usually caused by activation of inflammasome and caspase, plays an important role in the progress of HCC [4][5][6][7][8]. Pyroptosis pathways include canonical pyroptotic pathways mediated by caspase-1 dependence and non-canonical pyroptotic pathways mediated by caspase-4, − 5, and − 11.…”
Section: Introductionmentioning
confidence: 99%